A new approach to the thermodynamics study of drying tomatoes in mixed solar dryer. (15th November 2019) - Djebli, Ahmed; Hanini, Salah; Badaoui, Ouassila; Boumahdi, Mouloud
Highlights: The tomato samples to dry were cut in different thicknesses and wedges number. The effective diffusivity was calculated using Fick's diffusion equation. A new thermodynamic approach was evaluated and compared with a literature model. The drying in the present study conditions is spontaneous. Abstract: This work presents the results of an experimental study and thermodynamic study of solar drying of tomatoes of the KAWA type, where the drying experiments was carried out in a large scale mixed solar dryer. The aim is to obtain the drying curves and calculate the effective diffusivity to predict drying kinetics and thermodynamic characteristics of tomatoes drying. The tomato samples were cut in two different shapes namely flat slices and wedges. In the case of flat slices, there were four different thicknesses, 0.5, 1, 1.5, 2 cm. For the wedged slices, the tomatoes was slit into 2, 4, 8 and 16 equal sections. The moisture content of the tomatoes varied between 92.5 and 93.6%. The tomatoes were weighed regularly until moisture content fell between 18 and 25%. The Fick's diffusion equation was used to calculate the effective diffusivity from the experimental data by fitting a linear dependency. A new proposed approach from the Arrhenius equation and a literature model were used to determine thermodynamic parameters. The drying operation lasted from 5 h to 21.25 h for flat slices and 8.5 h to 28.25 h for the wedges. The thermodynamic parameters derived from the new proposed approach are compared with the literature model. Evidently, the Gibbs free energy values indicate that tomato solar drying is a spontaneous natural process.